QUANTITATIVE METHODOLOGY: BOARDING FROM THE COMPLEMENTARITY IN THE SOCIAL SCIENCES - Del Canto, Ero (2013)
Man has been in search of knowledge in the reality, however in the social sciences it changes. The article discusses quantitative’s research associated with the complementary of methods to address the social reality. We made a documental review: physics and electronic literature by different authors. The conclusions are focused on the importance of complementarity to approach to the object of study and understanding of social reality.